Graphene Oxide in Environmental Remediation Process - Pendolino, Flavio; Armata, Nerina (SpringerBriefs in Applied Sciences and Technology,, 2017)
This book discusses the remediation process using graphene oxide as removal agent from a chemical point of view. State of the art, properties of graphene oxide and its preparation methods are reported in the introduction. Environmental issues and regulations are presented in view of applying graphene oxide dispersion to the purification of aqueous medium, especially for industrial wastewater. The remediation process, for removal organic molecules, inorganic/metallic ions, covers the last part of the book. Future prospective for graphene oxide in the environmental remediation approach is commented.